Strategic planning, autonomous actions and corporate performance - Andersen, Torben Juul (2000)
Presents a recent research programme investigating the dual performance effects of strategic planning and autonomous actions in the strategy formation process. Discovers that strategic planning has positive performance effects across industries, and exists in tandem with autonomous actions, where managers make responsive decisions that enhance performance under changing environmental conditions.